Biodegradable Nanoparticles: Tumor Targeted Delivery of an Anti‐Cancer Therapeutic: An In Vitro and In Vivo Evaluation (Adv. Healthcare Mater. 2/2021). Issue 2 (20th January 2021) - Kang, You Jung; Holley, Claire K.; Abidian, Mohammad Reza; Madhankumar, Achuthamangalam B.; Connor, James; Majd, Sheereen
Abstract : This cover art represents a new anti‐cancer nanoformulation that targets the brain glioma tumors, offering a potential treatment for these aggressive tumors. In article number 2001261 by Sheereen Majd and co‐workers, biodegradable nanoparticles that carry a potent anti‐tumor chelator are decorated with targeting molecules to address and kill glioma tumor cells selectively while sparing the healthy cells.